Distribution and compartmental organization of GABAergic medium-sized spiny neurons in the mouse nucleus accumbens - Gangarossa, Giuseppe; Espallergues, Julie; De Kerchove D'Exaerde, Alban; El Mestikawy, Salah; Gerfen, Chip; Hervé, Denis; Girault, Jean-Antoine; Valjent, Emmanuel (Frontiers in Neural Circuits, 2013)
The nucleus accumbens (NAc) is a critical brain region involved in many reward-related behaviors. The NAc comprises major compartments the core and the shell, which encompass several subterritories. GABAergic medium-sized spiny neurons (MSNs) constitute the output neurons of the NAc core and shell. While the functional organization of the NAc core outputs resembles the one described for the dorsal striatum, a simple classification of the NAc shell neurons has been difficult to define due to the complexity of the compartmental segregation of cells. We used a variety of BAC transgenic mice expressing enhanced green fluorescence (EGFP) or the Cre-recombinase (Cre) under the control of the promoter of dopamine D1, D2, and D3 receptors and of adenosine A2a receptor to dissect the microanatomy of the NAc. Moreover, using various immunological markers we characterized in detail the distribution of MSNs in the mouse NAc. In addition, cell-type specific ERK phosphorylation in the NAc subterritories was analyzed following acute administration of SKF81297 (a D1R-like agonist), quinpirole (a D2R-like agonist), apomorphine (a non-selective DA receptor agonist), raclopride (a D2R-like antagonist), and psychostimulant drugs, including cocaine and d-amphetamine. Each drug generated a unique topography and cell-type specific activation of ERK in the NAc. Our results show the existence of marked differences in the receptor expression pattern and functional activation of MSNs within the shell subterritories. This study emphasizes the anatomical and functional heterogeneity of the NAc, which will have to be considered in its further study.